Transdisciplinary management of patients with disorders of sexual development in Colombia. Limiting factors for appropriate management (2017)
Introduction Disorders of sex development (DSD) are present in 0.76 per 4,500 births. The management is complex and requires the ability of a multi-disciplinary team, which can have a positive impact on the prognosis. The aim of this article is to describ